Medical Equipment Procurement Strategy Based on ASPAK Application at MABA District General Hospital, East Halmahera Regency - Seli Dela Sufiati; Dasrun Hidayat; Ign Wiseto P Agung (Training & Research Institute - Jeramba Ilmu Sukses, 2026)
Medical equipment procurement constitutes a strategic element in improving service quality, yet its implementation at MABA District General Hospital in East Halmahera Regency still confronts substantial structural and technical challenges. This study analyzes medical equipment procurement strategy based on the ASPAK (Application of Facilities, Infrastructure, and Medical Equipment) system across five focal areas: input components, data availability and accessibility in planning, procurement process implementation, training processes related to equipment utilization, and output effectiveness. Employing descriptive qualitative methodology through in-depth interviews with 15 key informants, observations, focus group discussions, and document analysis, the study reveals critical deficiencies: at the input level, absence of comprehensive Standard Operating Procedures for needs assessment, limited Human Resources capacity, and inadequate supporting infrastructure including unstable internet connectivity and insufficient room readiness crucial for ASPAK operations; at the process level, planning not fully based on ASPAK-driven gap analysis resulting in inaccurate prioritization and mismatches between equipment specifications and clinical needs, with acceptance procedures encountering technical verification barriers; at the output level, suboptimal utilization of procured devices due to unprepared facilities, uneven operator competency, and absence of structured post-procurement monitoring and evaluation mechanisms. Synthesis of findings demonstrates that ASPAK effectiveness depends critically on strengthening internal regulations, enhancing human resource capacity, ensuring infrastructural readiness, and implementing systematic monitoring-evaluation frameworks to optimize medical equipment procurement in island region hospitals.